The use of formative research to culturally adapt a psychosocial support program for perinatal Mayan women in Guatemala - Brieanne K. Kohrt; Mary Margaret Saltiel; Ethan L. Rosen; Melyna Cholotio (Elsevier, 2022)
Indigenous Mayan women in Guatemala are at increased risk for perinatal psychological distress due to higher base rates of anxiety, depression, and PTSD linked to oppression, poverty, and a legacy of femicide. This paper discusses the process of adapting the Thinking Healthy Program (THP), a task-sharing intervention that targets perinatal depression, for use within a community health organization serving indigenous, Tz'utujil Mayan families in the Sololá region of Guatemala.The cultural adaptation of scalable psychological interventions conceptual framework was used throughout the adaptation process. A formative, mixed-methods approach triangulated findings from 1) qualitative key informant interviews with perinatal community health workers (PCHWs) and local mothers, 2) observational mock-role plays between PCHWs and distressed perinatal women, 3) a self-report questionnaire examining stigma and culturally-sanctioned help-seeking approaches, and 4) consultation with local stakeholders.Results of this study suggest that the THP can be adapted for Tz'utujil Mayan women by centering the adaption on the cultural idiom of Qajnaq ruchojq'aq' (low force/energy). The explanatory model of Qajnaq ruchojq'aq' is interpersonal in nature, thus the integration of techniques from a low-intensity interpersonal therapy intervention are indicated. Symptoms of Qajnaq ruchojq'aq' were largely cognitive and behavioral, thus the primary treatment elements of the THP are well-aligned. Training adaptations were also identified, including addressing safety concerns and mental health stigma in the community. The next step is to pilot the adapted intervention, making iterative changes as necessary to best meet the psychosocial needs of Tz'utujil Mayan women. This model of adaptation, and findings regarding implementation of interpersonal elements and aspects to address safety, should be considered in future psychosocial programming for perinatal women in Latin American indigenous contexts.